TAGHYIRĀT AL-AUZAN AL-ARUDIYAH FI ṢYI’IR ‘ALA SAHIL AL-BAHR LANĀ GARĀBAH: DIRĀSAH TAHLILIYAH ARUDIYAH - Rosul, Moh. Sahumi; Roziki, Khafid (Annual International Conferences on Language, Literature, and Media, 2022)
The changes of wazan in a verse is normal so that poets can choose the correct sentence and does not harm the beauty in poetry associated with wazan . Prosody is still used until today, although many modern poets do not use it to write poetry, but rather use free poets unconstrained in wazan . Abbas Mahmoud al-Akkad is a modern Egyptian poet best known for a form of classical poetry that still follows formulas in prosody. The objectives of this research are: 1) to know the bahr used in the poetry of Abbas Mahmoud Al-Akkad; 2) To know the wazan changes that occur in his poem. The researcher used the qualitative descriptive approach by taking the subject of the research, the poetry of Abbas Mahmoud Al-Akkad, entitled "On the sea coast, we have a strangeness" in Al-Akkad's Diwan. The researcher obtained the data by downloading, reading and recording, and then verifying the validity of the data through a deep understanding. Data analysis was performed using the Miles and Huberman method through data reduction, data presentation, and conclusion. The results of this research are; 1) that the wazan used in his poetry is the wazan of ​​speed in all the verses; 2) Umm al-Zahhaf, which is mentioned in his poetry, is the scavenger of folding and al-Khuban, and in it is the reason for the fall, endowment and slack. The researcher also found some changes in wazan that are inconsistent with slips and ills, and the researcher concluded that these are errors in modern poetry.